The Burden of Uterine Fibroids from the Perspective of US Women Participating in Open-Ended Interviews - Elke Hunsche; Viatcheslav Rakov; Kayla Scippa; Brooke Witherspoon; Laura McKain (Mary Ann Liebert, 2022)
Background: Research on women's perspective of uterine fibroids (UF) experiences using their own words is limited. This study aimed to provide new insights on the symptoms experienced and their impacts on daily life. Methods: Interview substudy in 30 US women with heavy menstrual bleeding (HMB) associated with UF who completed one of two phase 3, randomized, double-blind, placebo-controlled trials (LIBERTY 1 and 2; ClinicalTrials.gov identifiers: NCT03049735, NCT03103087). Women who consented to participate in this substudy were interviewed after their last clinical trial study visit. Concepts (i.e., symptoms and impacts) of importance to women were determined via open-ended questions, and the frequency of symptoms and their impacts, including the relationship between pain and menstruation, were assessed. Data were analyzed using established qualitative research methods, including grounded theory and constant comparative methods, and concept saturation was assessed. Results: Fifteen unique symptoms of UF emerged: the most commonly reported were HMB (n?=?30, 100.0%), pelvic pain (n?=?28, 93.3%), and passing of blood clots (n?=?24, 80.0%). In total, 25 unique impacts were identified across eight concepts: physical impacts, activities of daily living, sleep, emotional impacts, sex life, social impacts, work and school, and financial impacts. Concept saturation was achieved for both symptoms and impacts. Conclusion: This study provides data on the symptoms experienced by women with HMB associated with UF, as well as the negative impacts of these symptoms as reported using their own words. The study findings confirm the significant burden associated with symptomatic UF.